Sistem Tanda dalam Tradisi Gowokan di Desa Babagan, Lasem: Perspektif Semiotika Saussure - Aprilia Filiauma; Ermi Dyah Kurnia; Prembayun Miji Lestari (Kawruh: Journal of Language Education, Literature and Local Culture, 2026)
Indonesia has a diversity of tribes, races, religions, and cultures that are reflected in local traditions that are passed down from generation to generation, such as the gowokan tradition in Babagan Village, Lasem District, Rembang Regency. Babagan Village which is located in the Lasem cultural area is known as part of the historical area in Lasem, Rembang Regency, Central Java, which has a wealth of traditions and cultural acculturation. Tradition is not only understood as a habitual practice that is passed down from generation to generation, but also as a symbol system that represents the values, beliefs, and outlook on life of the supporting community. This research aims to describe the practice of the gowokan tradition and analyze the sign system contained in it. The Grand theory used is Ferdinand de Saussure's structural semiotics regarding the relationship between the signifier and signified, with a theory supporting the post-structuralist perspective that states that one marker can produce a compound marker. This research uses a qualitative descriptive method with an interpretative approach. Research data in the form of informant speech, procession series, presentation symbols, and visual documentation. The data source was obtained from the village head, Mudin, traditional practitioners, and local elders through participatory observation, in-depth interviews, and documentation. Data analysis is carried out through data reduction, categorization, data presentation, and interpretation of meaning using syntagmatic and paradigmatic relations. The research results show that every element in the gowokan procession such as sega liwet, sayur kunci bayem, kunir rice, and dhuwit klithik is a signifier that has a signified value in the form of gratitude, hope, prosperity, and social harmony. The procession of throwing udhik-udhikan becomes a symbol of sharing sustenance and strengthening communal solidarity. This finding confirms that the gowokan tradition not only functions as a thanksgiving ritual, but also as a system of cultural signs that contains symbolic meanings that can be interpreted in layers by the community. Thus, the gowokan tradition can be understood as a cultural text that represents the Babagan people's view of life about the balance between humans, God, and their social community.